Efektivitas Pembiasaan Salat Duha Dalam Pencapaian Nilai-nilai Profil Pelajar Pancasila di SMP Negeri 13 Surabaya - Fanani, Miftakhul; Fahmi, Muhammad; Muhammad Hafidh Ubaidillah; Inayati, Nurul; Fitriyah, Latifatul (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2024)
Duha prayer is one of the habituation activities before learning which is carried out at SMP Negeri 13 Surabaya. The habit of praying Duha prayer is carried out with the aim that students are accustomed to carrying it out regularly, both at home and at school, and also aims to form religious character in students. With the Duha prayer, it is hoped that it can grow characters that are following the elements of the Pancasila student profile. This study was carried out to know the effectiveness of the habituation of the duha prayer carried out at SMP Negeri 13 Surabaya. A descriptive quantitative method was used with questionnaires and interviews to collect data from students and teachers regarding the habit of praying duha. The results showed that the habit of praying duha prayer was more effective than before, namely at the beginning of the study. Although it can be said to be effective, the habit of praying duha still needs to be improved so that its effectiveness can be increased even more.